A study of clinical and dermoscopic features in alopecia areata at a tertiary referral center - N., Nikhil; P., Mamatha; K., Hanumanthayya (International Journal of Research in Dermatology, 2020)
Background: Alopecia areata (AA) is a common chronic inflammatory disease causing unpredictable non scarring form of hair loss. Dermoscopy is a clear cut as well as valuable method done in a noninvasive manner to study the signs of alopecia areata. Aim was to elucidate the various clinical characteristics and dermoscopic findings of alopecia areata. Methods: A total of 150 patients were examined using a dermlite dermoscope at dermatovenereology OPD of Vydehi Hospital. Detailed history, clinical features, associated changes, severity and dermoscopic findings were noted. Results: In our study males (54.7%) were more than females (45.35%) with the ratio of 1.2:1. Mean age of the patients was 25 years. Mean duration of the disease was around 6 months. The most common type noted in our study was patchy alopecia (76%) and most common affected site was scalp (frontal and parietal region) (49.35%). 28% of the people have itching, otherwise it is mostly asymptomatic. Stress was a triggering factor in 24.70% patients. Nail changes in the form of pitting seen in 20.7% patients. The various dermoscopic findings observed in our study are yellow dots (80%), short vellus hair (74.7%), exclamation hair (34%), black dots (28%), broken hair (25.3%). Conclusions: Short vellus hair and yellow dots are seen in most cases of our study. They vary according to the activity of the disease and treatment. Yellow dots, black dots and tapering hair indicate active disease, while short vellus hairs indicate remission.